Phenotypic Characterization of Common bean (Phaseolus vulgaris L.) Accessions Conserved at the Genetic Resources and Biotechnology Institute: Experimental Investigation - Rudo Musango; Kusena Kudzai; Summerset Mhungu; Handsen Tibugari (New Visions in Science and Technology Vol. 11, 2021)
The goal of this study was to look at the variation in qualitative and quantitative features among ten accessions collected from Genetic Resources and Biotechnology Institute (GRBI) in Zimbabwe. The accessions were planted in a Randomized Complete Block Design, with three replicates. The common bean descriptor list from the International Board for Plant Genetic Resources (IBPGR) was used to capture qualitative and quantitative attributes. The quantitative data for the number of days to 50% flowering, plant height, days to maturity, seed size, grain yield, and number of seeds per pod were analyzed with Hierarchical Cluster Analysis Minitab Release 12.22 and GenStat Discovery 14 software. When the dendrogram was partitioned at the 26:22 percent similarity levels, cluster analysis split genotypes into two primary groups. Cluster A had two bean genotypes, while Cluster B had eight genotypes divided into two sub-groups. The genetic closeness of accessions varied greatly depending on genotype pairs, groups, and sub-groups. The genetic similarity between accessions from different clusters (A and B) was lower, while it was higher for accessions from the same cluster. The number of pods per plant, number of seeds per pod, length, and seed size all showed significant differences (P<0.01) amongst the accessions. It is possible to establish that morphological variation exists among the 10 common bean accessions based on distinct morphological features displayed by different accessions. It may also be concluded that among the ten most common bean accessions, there are no duplicates.